Optimizing Accessibility to Increase the Tourist Attraction of Florida Baths in Namukur Village, Sei Bingai District, Langkat Regency - Miya Aulina Lubis; Annisa Ilmi Faried; Ahmad Fadlan (Utan Kayu Publishing, 2025)
This research aims to optimize accessibility to increase tourist attractions in the Florida Baths of Namukur Village, Sei Bingai District, Langkat Regency. Using a qualitative descriptive approach, data is collected through interviews, documentation, and observations from tour guides, business actors, and local communities. The results show that inadequate road conditions, lack of direction signs, and limited transportation are the main obstacles. However, the natural beauty and the support of the local community is a significant strength. Increased accessibility is expected to increase the number of visitors and local income. SWOT analysis identifies the need for facility improvement and more aggressive promotion. In conclusion, investment in infrastructure and road facilities, along with community involvement and effective marketing strategies is very important for the sustainable development of tourism in the Florida Baths, while maintaining environmental and social sustainability)